E Purchasing Application to Improve Company Performance - Budiman; R Yadi Rakhman Alamsyah; Ismi Nur Muhamad; Nur Alamsyah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to create a web-based purchasing application. With the current purchasing system, there are often errors in data processing and also difficulties in searching for documents because there is no use of databases in the system. Therefore, an application is needed in the management of web-based purchasing data with the warerfall development method. While the analysis and design of the application is done with an object-oriented approach described by UML notation. This system is made using the php programming language and MySql database, the result of this research is the creation of a web-based data processing application that can be used by companies to facilitate the data processing process.